Basal condensation of Numb and Pon complex via phase transition during Drosophila neuroblast asymmetric division - Zelin Shan (Nature Portfolio, 2018)
Polarized localization of Numb and Pon in Drosophila neuroblasts (NBs) enables their unequal segregation during asymmetric cell divisions. Here, the authors demonstrate liquid-liquid phase separation of Pon and Numb in NBs mediated by multivalent intermolecular interactions is required for their basal condensation.